Back Cover: Simultaneous Assessment of Kinetic, Site‐Specific, and Structural Aspects of Enzymatic Protein Phosphorylation (Angew. Chem. Int. Ed. 36/2014). Issue 36 (10th July 2014) - van de Waterbeemd, Michiel; Lössl, Philip; Gautier, Violette; Marino, Fabio; Yamashita, Masami; Conti, Elena; Scholten, Arjen; Heck, Albert J. R.
<x xml:space="preserve">Abstract</x> Multiple aspects of protein phosphorylation can be addressed simultaneously by an analytical method described by A. J. R. Heck and co‐workers in their Communication on page 9660 ff. Their approach integrates native and bottom‐up mass spectrometry and provides insight into the site specificity, kinetics, and structural effects of this biochemical process.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>